Prophetic Parenting Mencetak Pendidik Berkarakter Dalam Pendidikan Anak Usia Dini - Muhammad Taufiqurrahman (IAIN Bengkulu, 2018)
Early childhood education is one of the efforts made by the government to start education in the early stages of child development. Through a psychological and educational approach, educators in early childhood must have the characters and competencies that have been implemented by the government in Government Regulation No.27 of 1990 Article 14 Paragraphs (1) and (2). This is a literature research which gathers theories dealing with early childhood educators referring to the Sunnah of the Prophet Muhammad SAW which is summarized in the terms of Prophetic Parenting. The results of the study are presented in the form of important points for person who is dedicated to becoming an early childhood educator. These points are some forms of character that must be owned by early childhood educators based on several Hadith of the Prophet Muhammad SAW. The characteristics of the educator who wants to succeedin his field are not in a hurry, gentle, compassionate, tolerant, not easy to get angry, proportionate and able to give advice. The results of this study are expected to be used by the head of PAUD to create the characters of early childhood educators in accordance with the teachings of the Prophet Muhammad SAW. Keywords: Prophetic Parenting, Character, Early Childhood Educator